Future changes in extreme events in Mozambique as simulated using the PRECIS regional climate modeling system - Pinto, Izidine S de Sousa (Department of Environmental and Geographical Science, 2015)
Future climate change is generally believed to lead to an increase in climate variability and inthe frequency and intensity of extreme events. Mozambique is well known for its occurrenceof severe weather and extreme climate events such as floods, tropical cyclones and droughts.Such events have serious impacts on the livelihoods of most people who often rely on subsistence agriculture.This dissertation explores possible changes in extremes in temperature and precipitation over Mozambique, based on high-resolution (25 km) simulations of the regional climate model system PRECIS (HadRM3P), forced by the ECHAM4 global mode.